'The role of percolation in hydrogel-based tissue engineering and bioprinting'. (September 2020) - Vernerey, Franck J.; Bryant, Stephanie
Abstract: Hydrogels provide an excellent material platform to be used as a structural scaffold in tissue engineering or as a bioink for bioprinting. Their mechanical and degradation properties must however be very well tuned so that they can simultaneously provide a continuous mechanical support to embedded cells and promote the growth of a new tissue. This constitutes a significant challenge that can be addressed by using a rational approach combining experiments and simulations. We show here that the solution to achieving continuous integrity during the hydrogel-to-tissue transition relies on the concept of mechanical percolation in an interpenetrating network made of hydrogel and neo-tissue. We particularly discuss how percolation theory predicts that the hydrogel must possess some heterogeneities, which may be achieved via localized modes of degradation and nonuniform cell seeding.